Zouping revisited : adaptive governance in a Chinese county - Oi, Jean C. (Jean Chun); Goldstein, Steven M. (Steven Martin) (Studies of the Walter H. Shorenstein Asia-Pacific Research Center., 2018)
This volume describes how one local government in China has governed a much larger and vastly more complex market economy without any outward changes in the formal institutions of government. The chapters document the subtle but profound changes in the way that established governing bodies operate in practice. Drawing on local fieldwork conducted over many years in a single county, the chapters describe the ways that county agencies have evolved through ad hoc bureaucratic adaptations that have profoundly altered the way that government organs operate.